2014
DOI: 10.1016/j.jaci.2013.12.024
|View full text |Cite
|
Sign up to set email alerts
|

IgE-mediated mast cell responses are inhibited by thymol-mediated, activation-induced cell death in skin inflammation

Abstract: Background Mast cells play a critical role in inflammatory skin diseases through releasing pro-inflammatory mediators; however, few therapies directly target these cells. In 1878, the use of topical Thymol, a now recognized potent agonist for Transient Receptor Potential (TRP) channels, was first described to treat eczema and psoriasis. Objective We sought to determine the mechanisms through which thymol may alter skin inflammation. Methods We examined the effect of topical thymol on IgE-dependent response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 63 publications
0
19
0
1
Order By: Relevance
“…For example, the results of Riella et al () suggested that thymol exhibited anti‐inflammatory activity and wound healing in a paw edema as well as peritonitis rodent models treated with thymol (10, 30, and 100 mg/kg). Using different in vitro and in vivo models, Wechsler et al () have also revealed that thymol promoted an activation‐induced apoptotic death of mast cells, which led to a suppression of subsequent IgE‐dependent responses to antigen. Thus, thymol could be used topically for the ablation of mast cell‐associated skin inflammation disorders (Wechsler et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the results of Riella et al () suggested that thymol exhibited anti‐inflammatory activity and wound healing in a paw edema as well as peritonitis rodent models treated with thymol (10, 30, and 100 mg/kg). Using different in vitro and in vivo models, Wechsler et al () have also revealed that thymol promoted an activation‐induced apoptotic death of mast cells, which led to a suppression of subsequent IgE‐dependent responses to antigen. Thus, thymol could be used topically for the ablation of mast cell‐associated skin inflammation disorders (Wechsler et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…PEC of NSG-SGM3 BLT mice were cultured to enrich for human mast cells and tested for calcium flux as described (13) . Briefly, mast cells were treated with 100 ng/mL chIgE-anti-NP overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Data from clinical and preclinical studies suggested that inflammatory cytokines increased in depressed patients and in animal models of depression, and the inhibition of the inflammatory processes might ameliorate their depressive symptoms [40]. Thymol exhibited strong anti-inflammatory activities in the models of osteoarthritis [20], asthma [21], skin inflammation [41], ear edema [42], and peritonitis [43] etc. It has been reported to attenuate inflammation through downregulating the expressions of proinflammatory cytokines, such as TNF-␣ [19,30,44], IL-1␤ [19], and IL-6 [19,44].…”
Section: Effects Of Thymol On Inflammationmentioning
confidence: 99%